Perkembangan Manajemen Keuangan Syariah: Tren dan Prospek Masa Depan - Julia Alfianti; Yeni Irawan; Anhar Firdaus; Mariana Mariana; Diana Diana; Dwi Meilvinasvita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze trends, challenges, and opportunities in Islamic financial management, focusing on technological innovation and regulation. The research employs a Systematic Literature Review (SLR) method, reviewing literature from various academic databases to identify recent developments in Islamic finance. The findings indicate that the growth of Islamic fintech, digitalization, and the adoption of technologies such as blockchain and AI have accelerated the transformation of this industry. However, challenges remain, including unstandardized regulations, low financial literacy, and limited access to Islamic financial services. Therefore, strengthening regulations, enhancing financial literacy, and optimizing digital technology are key factors in driving the sustainable growth of Islamic finance. With the right approach, Islamic finance has the potential to become an integral part of the global financial system.